If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + x = 38 Reorder the terms: x + 2y = 38 Solving x + 2y = 38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. x + 2y + -2y = 38 + -2y Combine like terms: 2y + -2y = 0 x + 0 = 38 + -2y x = 38 + -2y Simplifying x = 38 + -2y
| (3x+4)(x+8)= | | -5(x+2)=-(-5x+1)-x | | -4x^4+8x^3+60x^2=0 | | 0.16=56 | | -15t^3-12t-6=0 | | 35=y+2 | | 1+7n=8n+9 | | 6x+10=4x-32 | | 134x^2+308x+188=8x^2+4x+4 | | -48=-4r | | 0.2=0.004 | | 9x+63=-1 | | -2x-5.8=12.2 | | s=rx+tx | | 0.004=0.2 | | y+.666=4.75 | | W/4=88 | | 48.8=0.307t+50.1 | | 62z-(33z-38)= | | -6=3y+x | | 9x^5=36x^3 | | v/-6=2=-1 | | 5=2v^2 | | 4+-7x=1+-6x | | 11x^2+4x+5= | | 3/2x=3x/8 | | -420=30(-2b) | | 47=-7-3p | | 0.5-4forx=14.5 | | -5x+43=8 | | 1500+4p=1700+2p | | 6(m-19)=55/12 |